FEASIBILITY STUDY MATERIAL TECHNOLOGIES GLUEING EPLOIZOLYATSIONNYH AT FACADES HEAT INSULATION - , А. И., И. Н., А. А., В. К. (Municipal economy of cities (Technical science), 2013)
The article describes the main technological methods of fastening insulation in the construction of insulating facade systems with finishing plaster. It is shown that the optimal parameter for the economic and operational efficiency is the adhesive on the foam insulation is a continuous way, using a spatula the size of the tooth 4 mm.